Patterns of Monarch Site Occupancy and Dynamics in Iowa - Dinsmore, Stephen J.; Vanausdall, Rachel A.; Murphy, Kevin T.; Kinkead, Karen E.; Frese, Paul W. (Frontiers in Ecology and Evolution, 2019)
The monarch butterfly (Danaus plexippus) is the focus of large-scale habitat restoration efforts because of recent population declines. From 2006-2017 we monitored monarchs at >400 sites throughout Iowa to link site occupancy and colonization/extinction dynamics to the presence of milkweed, site-specific habitat metrics, and landscape context at differing spatial scales. We used a robust design occupancy model in Program MARK and a hierarchical model selection approach to estimate site occupancy, extinction and colonization probabilities, and detection probability. Occupancy models revealed that monarchs responded differently to landscape features, environmental conditions, and local habitat conditions for site occupancy, extinction, and colonization probabilities. For site occupancy, the mean patch size of grassland at the 1-km spatial scale had a positive effect (β_GrassPS1K= 0.94, SE = 0.54) while the percent of the landscape in woodland at the 200-m spatial scale had a negative effect (β_WoodPL200= -1.68, SE = 0.34). For extinction, there were additive effects of the percent of the landscape in woodland at the 100-m spatial scale (β_WoodPLAND100= 2.70, SE = 0.63), the interspersion of grassland at the 1-km spatial scale (β_GrassIJI1K= -2.30, SE = 0.63), and litter depth (β_Litter= 0.46, SE = 0.13). Finally, there were negative effects of the percent of the landscape in woodland at the 200-m spatial scale (β_WoodPLAND200= -4.67, SE = 1.37) and the interspersion of grassland at the 100-m spatial scale (β_GrassPS1K= -2.02, SE = 0.70) on colonization probability. Detection probability was affected by the additive effects of canopy cover and monarch density; no other detection model was competitive. In the top model there was a positive effect of monarch density (β_Density = 0.28, SE = 0.05) and a negative effect of canopy cover (β_Canopy=-0.18, SE = 0.03) on detection probability. In Iowa, monarchs are widespread on conservation lands where they avoid sites with lots of canopy cover. Colonization and extinction processes are influenced by an interplay of landscape attributes across multiple spatial scales and site habitat attributes. Our study provides the first comprehensive insight into monarch use of conservation lands in Iowa, and predicted responses to important covariates may be useful for future conservation efforts.